(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
This study examined the relationship between computer self-efficacy, data quality management, and service delivery among Health Information Management (HIM) professionals in Lagos tertiary hospitals. The study adopted a descriptive survey research design. The population consisted of three hundred and eighty-four HIM professionals across five tertiary hospitals in Lagos state. Total enumeration was adopted for the sample. The research instrument was a structured questionnaire adapted from theory and related literature. The method for data analysis consisted of both descriptive and inferential statistics. The results showed that computer self-efficacy of HIM professional (Adj.R2=0.152, p<0.05) and data quality management practices (Adj. R2 =0.117,p<0.05) has a positive correlation with the service delivery of HIM professionals in Lagos tertiary hospitals. Multiple regression analysis also showed that the combination of computer self-efficacy and data quality managementsignificantinfluence on the service deliveryamong HIM professionals in Lagos tertiary hospitals (Adj. R2=0.154,p<0.05). The study concluded that effective service delivery of HIM professionals depend on the interplay between individual competencies and systematic data management in healthcare services. It was therefore recommended that Healthcare institutions in Lagos should invest in training and professional development programs aimed at further enhancing the computer self-efficacy of HIM professionals. These initiatives should be ongoing, considering the rapidly evolving healthcare technology landscape.